A Study to Find Anatomic Measurement Correlating to Occlusal Vertical Dimension: Comparison in Two Ethnic Groups of Nepal (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: occlusal vertical dimension; rima oris to pupil distance; eye-ear distance; vertical height of ear